Politician as venture capitalist: Politically-connected VCs and IPO activity in China - Wang, Rouzhi; Wu, Chaopeng (Journal of Corporate Finance, 2020)
This study examines the impact of venture capitalists' (VC) political connections on their portfolio companies. Specifically, we use a manually-collected dataset of VCs' political connection to investigate the potential benefits and costs that politically-connected VCs bring to their portfolio companies. On the benefit side, we find that companies backed by politically-connected VCs are more likely to obtain IPO approval from the Chinese Securities Regulatory Commission (CSRC, China's counterpart to the SEC in the US). On the other hand, these VCs are more likely to acquire equity in the company at a significant discount and to invest shortly before the IPO application. In addition, we find that politically-connected VC-backed companies do not experience greater improvements in financial performance, corporate governance, or innovation output subsequent to receiving venture financing. Our results further show that companies backed by VCs with political connections are less mature and experience more underpricing at their IPO than non-politically-connected VC-backed companies. Finally, we find that, compared to non-politically-connected VCs, politically-connected VCs exit earlier after a company's IPO and that their portfolio companies experience greater post-IPO underperformance and performance volatility.